The changing phases of Malaysian economy - Okposin' Samuel Bassey (Pelanduk, 1999)
This book examines the changing phases of the Malaysian economy since independence in 1957. Agriculture was the main source of growth in the early phase of development. In the 1960s and 1970s, import-substitution and export-oriented indutralisation propelled economic growth. In the 1980s, investment and the growing service sector was the engine of growth. In the 1990s, the economy is sustained through productivity and industrial upgrading to higher value-added industries.